Spatial variability of organic carbon in sandy soils: Case study of Deliblato Sands (Serbia) - Kadović Ratko; Belanović-Simić Snežana; Perović Veljko; Lukić Sara; Miljković Predrag; Mansour Yousef Ali Bohajar; Olđa Marius (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2023)
This paper presents the results of the study and variability of organic carbon content in soils formed in the Deliblato Sands, a Special Nature Reserve (SNR). The sandy soils of Deliblato Sands are very sensitive to degradation, while the land use system is regulated by law. Analyzes were performed for soil layers 0-10 cm and 10-20 cm according to reference soil groups and identified vegetation groups. The mean values of SOC content (Soil Organic Carbon) (g/kg) are 23.13 (0-10 cm) and 11.20 (10-20 cm), while the values for SOCD (Soil Organic Carbon Density) (g/m2) are 2.40 (0-10 cm) and 1.22 (10-20 cm). The total reserves of SOC in the soils of the Deliblato Sands were estimated at 1.18×106 Mg in the upper layers (0-20 cm). Analyzes of the spatial variability of SOC (g/kg) and SOCD (g/m2) were carried out using GIS techniques in order to map the distribution of these parameters. A high degree of spatial variability was determined in terms of SOC content and density, both by reference soil groups and by vegetation groups. The obtained results show that in the management process of SNR Deliblato Sands, and therefore SOC reserves, attention should be focused on the protection of autochthonous vegetation.